Expression of cytosolic and membrane associated tissue transglutaminase in rat hepatic stellate cells and its upregulation during transdifferentiation to myofibroblasts in culture - Schnabel, Claudia; Sawitza, Iris; Tag, Carmen G.; Lahme, Birgit; Gressner, Axel M.; Breitkopf-Heinlein, Katja (Hepatology research, 2004)
Transdifferentiation of hepatic stellate cells (HSC) to collagen producing myofibroblasts (MFB) is a principal event in liver fibrogenesis. In our studies we investigated if tissue transglutaminase (tTG) from these cell types may play a role in liver fibrosis. Separation of cytosol and membrane components showed membrane associated tTG and during transdifferentiation an upregulation of total tTG on mRNA and protein level was found, but no modulation during stimulation with TGF-β1. In HSC and fully differentiated MFB a significant amount of the total tTG synthesised during transdifferentiation is found to be membrane-associated whereas the remaining portion is cytosol-associated and only very little is found within the extracellular matrix (ECM). The data implicate that tTG in this cell type seems to play an important role in liver fibrogenesis.